Diagnosing late-onset PKU in the shadow of refractory seizures - Ameer Awashra, MD; Haroun Neiroukh, MD; Aya Milhem, MD; Dawoud Hamdan, MD; Asmaa Sarama, MD; Tasneem Dweikat, MD; Alaa Hmeedan, MD; Samih Khader, MD (Radiology Case Reports)
Phenylketonuria (PKU), a rare autosomal recessive metabolic disorder, often presents with severe neurological complications if untreated, but late diagnosis can mimic other conditions such as Febrile Infection-Related Epilepsy Syndrome (FIRES). This report discusses a 10-year-old male initially misdiagnosed with FIRES, whose refractory seizures and encephalopathy prompted further genetic investigation. Whole-exome sequencing revealed compound heterozygous mutations in the PAH gene, confirming late-diagnosed PKU. The presence of pathogenic mutations in distinct locations within the PAH gene suggests the patient is a compound heterozygote, confirming a rare, late-diagnosed case of PKU. The case emphasizes that untreated PKU can result in toxic phenylalanine accumulation, leading to profound neuropsychiatric and cognitive impairments, which can be mitigated with early dietary intervention and lifelong management strategies.